Dokazi o učinkovitosti ortopedskih čevljev in vložkov - Burger, Helena (Rehabilitacija (Ljubljana), 2011)
The article reviews the literature about effectiveness of insoles or foot orthoses and orthopaedic shoes for paediatric pes planus, juvenile idiopathic arthritis, pes cavus, plantar fasciitis, hallux valgus, diabetic foot, fractures of foot and ankle and rheumatoid arthritis.
Keywords: okvare stopala; ortopedski čevlji; ortopedski vložki